Porroglossum raoi, a new species of Pleurothallidinae (Orchidaceae) from Ecuador - Baquero R., Luis E. (2017)
A new species of Porroglossum (Pleurothallidinae), Porroglossum raoi Baquero & Iturralde, apparently endemic to a cloud forest close to Chical, is described here. Porroglossum raoi is compared to known species within the genus growing close to the area where it was discovered. The big white flower, the thick, subclavate and brown-purple lateral sepal tails, a single subacute angle on the lower margin of the petals and a strong cinnamon and clove smell, immediately separates this from other species in Porroglossum. Taxonomical and ecological notes are given.